2016
DOI: 10.1016/j.scitotenv.2016.06.133
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and adsorption of isoproturon, tebuconazole, chlorpyrifos and their main transformation products under laboratory and field conditions

Abstract: Assessment of dissipation constitutes an integral part of pesticides risk assessment since it provides an estimate of the level and the duration of exposure of the terrestrial ecosystem to pesticides. Within the frame of an overall assessment of the soil microbial toxicity of pesticides, we investigated the dissipation of a range of dose rates of three model pesticides, isoproturon (IPU), tebuconazole (TCZ), and chlorpyrifos (CHL), and the formation and dissipation of their main transformation products followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…Although no systematic changes in the diversity and composition of the soil bacterial community were observed in response to CHL exposure, amplicon sequencing analysis identified a slight but significant change in the β-diversity of soil bacteria at 56 days in the microcosm experiment. Interestingly, this coincided with the formation of the maximum levels of 3,5,6-trichloropyridinol (TCP), the main hydrolysis product of CHL, in the soil which received the 10x dose (Papadopoulou et al, 2016 ). In contrast, in the field experiment, where CHL rapidly dissipated and high TCP concentrations were not observed (probably due to TCP leaching toward groundwater out of the examined soil layer), both the α- and β-diversity was not significantly altered when examined by NGS (although PhyloChip analysis proposed a slight but significant CHL effect at 70 days in the field study).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although no systematic changes in the diversity and composition of the soil bacterial community were observed in response to CHL exposure, amplicon sequencing analysis identified a slight but significant change in the β-diversity of soil bacteria at 56 days in the microcosm experiment. Interestingly, this coincided with the formation of the maximum levels of 3,5,6-trichloropyridinol (TCP), the main hydrolysis product of CHL, in the soil which received the 10x dose (Papadopoulou et al, 2016 ). In contrast, in the field experiment, where CHL rapidly dissipated and high TCP concentrations were not observed (probably due to TCP leaching toward groundwater out of the examined soil layer), both the α- and β-diversity was not significantly altered when examined by NGS (although PhyloChip analysis proposed a slight but significant CHL effect at 70 days in the field study).…”
Section: Discussionmentioning
confidence: 97%
“…This is in accordance with one of the limitations of long-term soil microcosm experiments causing changes in microbial abundance, composition, diversity and activity due to the lack of nutrient inputs (Edwards et al, 1997 ). In our study, the duration of the microcosm experiment was extended to 100 days in order to accommodate the long persistence of CHL, IPU and TCZ (10x dose rate) in the given soil with DT 90s of 96, 85 and 316 days, respectively (Papadopoulou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, our results also indicated that TEB has relatively greater contact toxicity than that of TBM. The low toxicity of TEB to earthworms in the artificial soil might be due to the fact that TEB can be easily adsorbed by the soil particles, which nevertheless reduces its bioavailability, exposure and toxicity to earthworm in the soil environment 35 . Apart from individual effects, the combined effects of two or more pesticides could be either greater or less than that predicted ones depending on individual or combined dose, pesticides chemistry, and organisms metabolic response 36 38 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that TEB has a moderate adsorption but TBM presents a low adsorption in different soils (Kotoula-Syka et al, 1993;Álvarez-Benedí et al, 1998;Cadková et al, 2013;Papadopoulou et al, 2016). Therefore, the experiment on the adsorption isotherms of both pesticides was not carried out in the present study.…”
Section: Degradation Of Teb and Tbm Alone And Combined Application Inmentioning
confidence: 93%